Association of mtDNA M/N haplogroups with systemic lupus erythematosus: a case-control study of Han Chinese women - Tang, Youzhou (Sci Rep, 2015)
To investigate whether mitochondrial DNA haplogroups M or N are related to occurrence or manifestations of systemic lupus erythematosus (SLE), we collected M/N haplogrouping and clinical characteristics from 868 Han Chinese women with SLE, as well as for 870 age-matched healthy Han Chinese control women. M/N haplogroups were determined in all subjects using allele-specific amplification. The frequency of M haplogroup in all patients was 429 (49.4%) and the frequency of N haplogroup, 439 (50.6%). The corresponding frequencies in controls were 456 (52.4%) and 414 (47.6%) (P = 0.213). Among women older than 50 years at onset age, the N haplogroup was significantly higher in patients than in healthy controls (59.6% vs 41.7%, P = 0.042). The N haplogroup was associated with significantly higher risk for certain SLE characteristics: hematological system damage (OR 2.128, 95%CI 1.610 to 2.813), skin impairment (OR 1.873, 95%CI 1.428 to 2.457), neurological disturbance (OR 3.956, 95%CI 1.874 to 8.352) and alopecia (OR 1.322, 95%CI 1.007 to 1.737 ). Our results suggest that in Han Chinese women, the mtDNA N haplogroup is associated with higher risk of late-onset SLE, skin impairment, neurological disturbance, hematological system damage and alopecia.